Encuentros-desencuentros del teatro de corral y de palacio - Díez Borque, José María (Anuario Calderoniano, 2014)
En palacio no sólo se representaban obras de gran aparato y tramoya, sino, de forma muy destacada, las mismas, o semejantes, obras escenificadas en los corrales de comedias. Se estudian los acuerdos y desacuerdos entre el teatro de palacio y el teatro de corral, teniendo en cuenta los excesos económicos del teatro cortesano y las protestas que ello produjo. «Similarities and Distinctions between Public and Court Theatre» The plays performed in the palace were not exclusively large spectacular productions but also, and most striking, the same or similar plays as in the public theatres were performed here. In this context, I study the similarities and distinctions between public and court theatre, paying attention to the economic excesses of the court theatre and the protests that they produced. PALABRAS CLAVE / KEYWORDS: teatro de corte, teatro público, excesos, costes, relaciones entre teatro de corte y teatro público / court theatre, public theatre, excesses, costs, relations between courtly and public theatre.